2024
DOI: 10.1111/bph.16308
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, a novel inhibitor of fatty acid binding protein 5, inhibits cervical cancer metastasis by suppressing fatty acid transport into nucleus and downstream pathways

Xiao Chen,
Jing Tian,
Chunyuan Zhao
et al.

Abstract: Background and PurposeBecause of cervical cancer (CC) metastasis, the prognosis of diagnosed patients is poor. However, the molecular mechanism of and therapeutic approach for metastatic CC remain elusive.Experimental approachIn this study, we first evaluated the effect of resveratrol (RSV) on CC cell migration and metastasis. Via an activity‐based protein profiling (ABPP) approach, a photoaffinity probe of RSV (RSV‐P) was synthesized, and the protein targets of RSV in HeLa cells were identified. Based on targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(102 reference statements)
0
0
0
Order By: Relevance
“… Jeong et al (2013) showed that RES attenuates lysophosphatidic acid-induced OC invasion by inhibiting epidermal growth factor receptor activation. According to Chen et al (2023) , RES effectively curtails the migration and metastasis of CC cells and improves survival rates in murine models. Specifically, by directly binding to fatty acid binding protein 5 (FABP5), RES competitively inhibits fatty acid binding to FABP5, consequently inhibiting MMP-2 and MMP-9 expression.…”
Section: Role Of Res In Inhibiting Metastasis and Tumor Cell Invasionmentioning
confidence: 99%
“… Jeong et al (2013) showed that RES attenuates lysophosphatidic acid-induced OC invasion by inhibiting epidermal growth factor receptor activation. According to Chen et al (2023) , RES effectively curtails the migration and metastasis of CC cells and improves survival rates in murine models. Specifically, by directly binding to fatty acid binding protein 5 (FABP5), RES competitively inhibits fatty acid binding to FABP5, consequently inhibiting MMP-2 and MMP-9 expression.…”
Section: Role Of Res In Inhibiting Metastasis and Tumor Cell Invasionmentioning
confidence: 99%